2011
DOI: 10.1021/jf2013474
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic Ketones from Ruta chalepensis (Rutaceae) Induce Paralysis on Root Knot Nematodes

Abstract: This paper reports on the use of Ruta chalepensis L. extracts as a potential nematicide against root knot nematodes Meloidogyne incognita and Meloidogyne javanica . The essential oil (REO) and methanol extract (RME) of R. chalepensis were tested against second-stage juveniles, with REO inducing paralysis in both species (EC(50/1d) = 77.5 and 107.3 mg/L) and RME being selective for M. incognita (EC(50/1d) = 1001 mg/L). Chemical characterization of extracts was done by means of GC-MS and LC-MS, revealing mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 33 publications
4
66
1
1
Order By: Relevance
“…graveolens EOs herewith studied showed very good B. xylophilus anti-nematodal activity. Ruta chalepensis EOs, also 2-undecanone rich, showed also high activity against the root knot nematodes Meloidogyne incognita and M. javanica (Ntalli et al, 2011a).…”
Section: Composition Of Essential Oils and Fractions Containing Hydromentioning
confidence: 97%
“…graveolens EOs herewith studied showed very good B. xylophilus anti-nematodal activity. Ruta chalepensis EOs, also 2-undecanone rich, showed also high activity against the root knot nematodes Meloidogyne incognita and M. javanica (Ntalli et al, 2011a).…”
Section: Composition Of Essential Oils and Fractions Containing Hydromentioning
confidence: 97%
“…In fact, according to Ben-Bnina et al (2010) and Haddouchi et al (2013), R. chalepensis essential oil where the major compound is a ketone, has strong antifungal and antibacterial activities. Interestingly, Ntalli et al (2011) reported for the first time an irreversible nematicidal activity of ketones as constituents of R. chalepensis against Meloidogyne javanica and M. incognita.…”
Section: Discussionmentioning
confidence: 99%
“…Ntalli et al (2011) reported the nematicidal activity of 2-undecanone as principal constituents of R. chalepensis essential oil against Meloidogyne javanica and M. incognita. Additionally, 2-undecanone has already been reported to exhibit nematicidal activity against M. incognita but as a constituent compound of the plant growth-promoting rhizobacteria Bacillus megaterium (Huang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of essential oils of aerial parts of R. chalepensis grown in many countries has shown a wide range of variations even in their major constituents (9)(10)(11)(12)(13)(14). However, few studies investigated the chemical composition of R. chalepensis essential oil from Tunisia.…”
mentioning
confidence: 99%